2022
DOI: 10.1093/ejo/cjab076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of self-etch primers with conventional acid-etch technique for bonding brackets in orthodontics: a systematic review and meta-analysis

Abstract: Summary Background Bonding with self-etch primers (SEPs) is one of the most popular systems for attaching orthodontic brackets to the enamel surface. There are conflicting reports about the efficacy and success of these systems compared with acid-etch (AE) bonding. Objective This systematic review and meta-analysis was performed to compare SEP with conventional AE technique for bonding bracke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Kerayechian et al [ 30 ] found that the bracket bonding failure and ARI score were not significantly different between self-etch and conventional acid-etch technique for bonding brackets.…”
Section: Discussionmentioning
confidence: 99%
“…Kerayechian et al [ 30 ] found that the bracket bonding failure and ARI score were not significantly different between self-etch and conventional acid-etch technique for bonding brackets.…”
Section: Discussionmentioning
confidence: 99%